4m^3n-4m^2n^2+mn^3-mn因式分解
3个回答
=4m^2n(m-n)+mn(n^2-1)
=mn(4m^2-4mn+n^-1)
=mn(2m-n+1)(2m-n-1)
相关问题
因式分解m^3-2m^2n+mn^2-4m^2+4mn+4m
已知m-n=4,mn=-1,求:(2mn+2m+3n)+(3mn+2n-2m)-(m+4n+mn)
已知m-n=4,mn=-1,求:(-2mn+2m+3n)-(3mn+2n-2m)-(m+4n+mn)的值.
已知m-n=4,mn=-1,求:(-2mn+2m+3n)-(3mn+2n-2m)-(m+4n+mn)的值.
已知m-n=3,mn=-3,求(-m-4n-mn)-(2mn-2m-3n)-(3mn+2n-2m)的值
4(-2mn+2m+3n)-2(3m+5n-mn),其中m+n=3,mn=-1
1.若m-n=4,mn=1,求(9-2mn+2m+3n)-(3mn+2n-2m)-(m+4n+mn)的值
1:已知m-n=4,mn=-1,求(-2mn+2m+3n)-(3mn+2n-2m)-(m+4n+mn)的值?
计算:[-m^3n/(m-n)^2]^4*[(n^2-mn)/m]^3/m^4n^10*[(mn-n^2)/m]^6
已知m-n=5,mn=-3,求-(m+4n-mn)-(2mn-2m-3n)+(2n-2m-3mn)的值.